Constraints on the Parameters of a U(1)B-L Gauge Boson - Williams, Matthew R. (My University, 2009)
The stability of the proton provides a strong constraint on models with baryon number-violating physics arising at a scale M< 1015 GeV. In such cases, an additional gauge symmetry is often introduced in order to make such models phenomenologically viable. Here, we consider the particular case where the Standard Model is extended to include an additional U (1) gauge boson that couples to baryon number minus lepton number (B - L). Constraints are obtained on such a field's gauge coupling, mass, and kinetic mixing coefficient (which controls the strength of mixing between it and the hypercharge U (1) present in the Standard Model). We derive updated bounds, relevant to the mass range from 1 keV to 10 TeV, by considering changes in primordial nucleosynthesis, in neutrino scattering, and in several precision electroweak observables. These constraints are overlaid in order to determine the best constraints on the gauge coupling, as a function of mass, at various values of the kinetic mixing parameter.
Keywords: Physics; Physics